Biotransformation of quercetin, kaempferol and apigenin to monoglycosylated derivatives by in vitro suspension cultures of Astragalus vesicarius ssp. carniolicus - Pavlinka Popova; Yancho Zarev; Iliana Ionkova (Pensoft Publishers, 2021)
Biotransformation of exogenous substrates quercetin, kaempferol and apigenin by suspension cultures of Astragalus vesicarius ssp. carniolicus to their monoglycosylated derivatives was performed. The maximal enzymatic potential of cells of A. vesicarius ssp. carniolicus was evaluated by different concentrations of substrate exposure. According to quantitative ultra-high performance liquid chromatography-high resolution electrospray ionization mass spectrometry (UHPLC-HR-ESI-MS) analysis, the highest concentration of kaempferol O-glycoside (14.88 nmol/g dry weight, DW), apigenin O-glycoside (10.55 nmol/g DW) and quercetin O-glycoside (150.83 nmol/g DW) was achieved, when suspension cultures were treated with 4 mg/mL kaempferol, 4 mg/mL apigenin and 3 mg/mL quercetin, respectively. The glycosidic products of biotransformation were not detected in the untreated control.